Roggendorf, Joseph (ed.), Studies in Japanese Culture, Tradition and Experiment. Sophia University Press, Tokio, 1965. (Monumenta Nipponica Monographs, núm. 23.) 276 pp. - F., C. (Estudios de Asia y África, 1969)
-